Familial Lamellar Ichthyosis in 6 Years Old and 2 Years Old Children: A Rare Case Report - Endra Yustin Ellistasari; Suci Widhiati; Ervina Rosmarwati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Lamellar ichthyosis (LI) is a rare non-syndromic congenital ichthyosis and is autosomal recessive. LI patients are generally born with abnormalities of keratinization, then develop into lamellar scales and persist into adulthood. This study aimed to describe cases of lamellar ichthyosis and provide appropriate management to prevent worsening patient prognosis. Case presentation: A 6-year-old girl and her younger brother, 2-year-old have been complaining of scaly skin all over their bodies since birth. Both patients were born with a history of being covered by a collodion membrane. On physical examination, thick and wide lamellar scales were seen with an erythematous base and palmoplantar hyperkeratosis. Ectropion of the eyelids, eclabium in the mouth area, and microtia in the ears were seen. The results of the dermoscopy examination showed brownish quadrilateral structures with white scales forming a lamellar pattern. Laboratory examination showed vitamin D insufficiency. Both patients were referred to the Pediatric Polyclinic regarding insufficiency and developmental complaints. Patients received therapy in the form of moisturizers, artificial eye drops, topical urea as a keratolytic, and oral vitamin D 2,000 IU per day. There was a clinical improvement after 3 months of treatment. Conclusion: Lamellar ichthyosis is an autosomal recessive congenital ichthyosis with clinical manifestations limited to the skin. In a minority of cases, LI can be inherited in an autosomal dominant manner. Thorough management is necessary to prevent a poor prognosis in patients.